The mental health and adjustment problems among first-year students in the Faculty of Humanities, University of Limpopo, South Africa : an attachment approach - Mosehane, Tshililo Cindy (My University, 2024)
The current study assessed the mental health and adjustment problems experienced by first-year university students in the Faculty of Humanities at the University of Limpopo. The sample consisted of 366 first-year university students. Both females (n=251) and males (n=115) were presented. A quantitative, cross-sectional design and simple random sampling were employed. Data was collected using the Student Adaptation to College Questionnaire (SACQ), General Health Questionnaires (GHQ-12), and Parental Bonding Instrument (PBI). Methods of analysis data were correlation (Spearman’s), factor analysis, and ordinal logistic regression to establish a relationship. Results revealed that there was a positive relationship between mental health and adjustment problems among first-year university students. Female students were reported to have the highest risk of experiencing mental health problems than male students’ mental health and adjustment problems are common among first-year university students between the ages of 18-21 years. The findings of this study also found that residence and socioeconomic status have an impact on the experience of mental health problems among university first-year students. Staying on campus for female students was regarded as safer than staying campus as such they reported fewer sleep challenges. The presence or absence of caring or over-caring parents does not significantly predict mental health problems among first-year university students.
Thesis (M.A. (Psychology)) -- University of Limpopo, 2024
Keywords: Mental health problems; Socioeconomic status; University first-year students; Mental health; Anxiety; Adjustment (Psychology); College freshmen; College students